(untitled) (Historia, 2021)
With the encouragement and support of the University of South Africaand in particular, of Professor S. Pauw, the University’s Principal, I under-took a tour of Europe and America to study modern methods of teachingRussian. During my travels I visited Washington D.C. in January, 1962and there I met Dr. S. Yakobson who is in charge of the Slavic Sectionof the Library of Congress. I asked him if he knew of any documentsgiving information about the Russian attitude towards the Boers during theAnglo-Boer War. He told me of a publication he had seen, which hadappeared in the Soviet "Krassni Arkhiv" (Red Archive) during the lastWar, which was for the first time printing documents, up to then kept secretin the Intelligence Dept. files (and later transferred to the Historical WarArchives).